Apparatus for calculating and correcting deflection of central axis of an obstacle detecting apparatus mounted on a vehicle, and system for controlling distance to a preceding vehicle travelling ahead - HIBINO, KATSUHIKO; NISHIMURA, TAKAO; SHIRAI, NORIAKI (1998)
The present invention aims to facilitate easy correction of the center axis of an obstacle detecting apparatus for a vehicle by calculating deflection of the center axis with respect to the vehicle. Each of most obstacles recognized as moving objects is a preceding vehicle 93, and when the subject vehicle 91 is moving straight, the preceding vehicle 93 is detected in a position straight ahead of the subject vehicle 91. If the optical axis 95 of the transmitting/receiving section 31 is oriented straight ahead of the subject vehicle 91, the preceding vehicle 93 will be detected on the optical axis 95. On the other hand, when the optical axis 95 deviates from the center axis of the vehicle, the preceding vehicle 93 is detected in a position deviated from the optical axis 95 by an angle m. In this case, the value of deflection of optical axis 95 is equal to - m. In addition, by determining whether or not the relative velocity vector component of an obstacle is within a given range, the accuracy of calculation can be bettered with data of vehicles moving in an adjacent lane and data of vehicles moving along a curve being removed.